Persuadable how great leaders change their minds to change the world - Al Pittampalli (New York, NY Harper Business, 2016)
"In Persuadable, you'll learn how Ray Dalio became the most successful hedge fund manager in the world by strategically curbing confidence. How Alan Mullaly saved Ford Motor Company, not by staying the course, but by continually changing course. How one Nobel Prize-winning scientist discovered the cause of ulcers by bravely doubting his own entrenched beliefs. You'll learn how Billy Graham's change of heart helped propel the civil rights movement, and how a young NFL linebacker's radical new position may prove to alter the world of professional football as we know it."--Amazon.com.
Includes bibliographical references and index
Keywords: Leadership